Forage species introduction and evaluation on semicleared ancient levees in the Nhecolândia subregion of the Brazilian Pantanal - Aníbal Comastri Filho, José; Pott, Arnildo (Pesquisa Agropecuaria Brasileira, 1998)
Beef cattle production is the main economic activity in the Nhecolândia subregion, but the production rates are low. Cattle feed on native grasses, which are subject to seasonal variation, having low nutritive value in the dry season and decreased availability during the flooding season. Due to these conditions, ranchers are growing pastures on cleared "cordilheiras", trying to solve the problem of feeding the animals. To fulfill the demand in the search for forage species and decrease the loss of soil nutrients, the Centro de Pesquisa Agropecuária do Pantanal (Pantanal Agricultural Research Center) carried out a program of forage evaluation in order to select species for areas of semicleared "cordilheiras". Eighty-seven species were tested in this enviroment. For each species two plots were used – with and withont fertilizer –, both divided in two subplots, one for dry matter production measurement and the other, untouched, for phenological observations. The technical criteria of evaluation were based on conventional parameters, in addition to measurements that allowed calculating a forage evaluation index (EI). This index indicated that the most promising grasses were Brachiaria decumbens (EI = 2.95) and B. humidicola (EI = 2.87), both on fertilized and unfertilized plots. Calopogonium mucunoides (EI = 2.75), both on fertilized and unfertilized plots, was the most promising legume species.